Development of Teaching Modules for Operation and System Stability Courses as a Pilot Project for the Electrical Engineering Study Program Towards Independent Learning - Sujito; Aripriharta; Mohammad Rodhi Faiz; Moh. Zainul Falah; Abdullah Iskandar Syah (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2022)
The challenges of the future of education are increasingly complex. The position of educators in the era of the industrial revolution 4.0 tends to be a facilitator who provides the latest information regarding the development of science. Merdeka Learning is an independent and versatile higher education learning model designed to create an unrestricted creative learning community. This development research resulted in teaching material in the form of learning modules and videos for the Operations and System Stability course. The process of developing modules/teaching materials uses the ADDIE development model, namely Analysis, Design, Development, Implementation, and Evaluating. The teaching materials developed are suitable for students to use based on the results of the formative test data and the Likert scale with 86%-100% being very good criteria. In the one-on-one trial, the percentage of expert eligibility was 94.5% for digital modules, and 92% for learning videos. In a small group trial taken from 7 TE 2017 and TE 2018 students, the percentage of eligibility results was 94% for digital modules, and 94.5% for learning videos. Meanwhile, in the field trials taken from 76 students of TE 2017 and TE 2018 the results of the feasibility percentage were 91% for digital modules and 90% for learning videos.